Cyclical patterns of employment, utilization and profitability - Ben Zipperer; Peter Skott (University of Massachusetts, Department of Economics, 2010)
The interaction between income distribution, accumulation, employment and the utilization of capital is central to macroeconomic models in the 'heterodox' tradition. This paper examines the stylized pattern of these variables using US data for the period after 1948. We look at the trends and cycles in individual time series and examine the bivariate cycical patterns among the variables.
Keywords: E12; E32; O41; 330; growth; business cycles; aggregate demand; instability; income distribution; utilization rate; investment function; pricing